The role of necroptosis in common respiratory diseases in children - Ning, Junjie; Qiao, Lina (Frontiers in Pediatrics, 2022)
Studies have shown that necroptosis (NEC) relies on a unique gene-regulated molecular pathway to cause cell death. With the development of knockout mouse models and specific molecular inhibitors of necrotic proteins, this cell death pathway has been considered one of the important causes of the pathogenesis of human diseases. In this review, we explored the possible roles and mechanisms of NEC in common respiratory diseases in children, such as acute lung injury, acute respiratory distress syndrome, pulmonary infection, childhood asthma, pulmonary hypertension, etc, in order to provide new ideas for the prevention and treatment of such diseases.